An overview of viral mutagenesis and the impact on pathogenesis of SARS-CoV-2 variants - Khan, Muhammad Zafar Irshad; Nazli, Adila; Al-furas, Hawaa; Asad, Muhammad Imran; Ajmal, Iqra; Khan, Dildar; Shah, Jaffer; Farooq, Muhammad Asad; Jiang, Wenzheng (Frontiers in Immunology, 2022)
Viruses are submicroscopic, obligate intracellular parasites that carry either DNA or RNA as their genome, protected by a capsid. Viruses are genetic entities that propagate by using the metabolic and biosynthetic machinery of their hosts and many of them cause sickness in the host. The ability of viruses to adapt to different hosts and settings mainly relies on their ability to create de novo variety in a short interval of time. The size and chemical composition of the viral genome have been recognized as important factors affecting the rate of mutations. SAR-CoV-2 (Covid-19) is a novel viral disease that has quickly become one of the world’s leading causes of mortality, making it one of the most serious public health problems in recent decades. The discovery of new medications to cope with Covid-19 is a difficult and time-consuming procedure, as new mutations represent a serious threat to the efficacy of recently developed vaccines. The current article discusses viral mutations and their impact on the pathogenicity of newly developed variants with a special emphasis on Covid-19. The biology of Covid-19, its mutations, pathogenesis, and treatment strategies are discussed in detail along with the statistical data.